Full Scale Application of Integrated Upflow Anaerobic Filter (UAF)-Constructed Wetland (CWs) in Small Scale Batik Industry Wastewater Treatment - Novarina Irnaning Handayani; Rustiana Yuliasni; Nanik Indah Setianingsih; Agung Budiarto (Balai Besar Standardisasi dan Pelayanan Jasa Pencegahan Pencemaran Industri, 2020)
This research aimed to evaluate the implementation of integrated Upflow Anaerobic Filter (UAF)-Constructed Wetlands (CWs) in real condition of wastewater treatment plant in batik small scale industry. The full scale reactor consisted of equalization chamber with HRT of 2 days; Upflow Anaerobic Filter (UAF) with HRT of 6 days, and Horizontal Subsurface Constructed Wetlands (HSSCWs) with HRT of 1.5 days. The UAF- CWs integrated technology was used to treat batik wastewater with COD inlet of 1339 – 2034 mg/L and pH of 9.0 – 9.4. This study showed that single UAF technology alone was able to reduced 56 – 78%, while the integration UAF –wetland technology improved the performance to 85% and reduced the pH into 7.5 – 7.8